Chapter 9: The optics of mixed methods research in the accounting field (2015-2020): a case of the untrained eye or methodological tunnel vision? - Reynolds, Giao (Edward Elgar Publishing, 2023)
Mixed methods research (MMR) has grown over past decade, indicating acceptance of mixed and multiple methods and methodological innovation within business and management research. This chapter presents MMR prevalence study findings from four quality accounting journals: Accounting, Organizations and Society (AOS), British Accounting Review (BAR), Critical Perspectives on Accounting (CPA), Management Accounting Research (MAR). Content analysis was applied to the methodologies employed in articles published in these journals during 2015-2020, finding a low rate of MMR studies ranging from 2.5 per cent to 4.9 per cent of non-conceptual articles. Among MMR publications (n=19, 2.9 per cent of non-conceptual studies), very few referred to substantive MMR foundational literature. Quantitative methods dominated BAR, AOS and MAR whereas qualitative methods dominated CPA. This study makes a significant contribution to scant MMR literature in the accounting field, first examined by Grafton et al. over a decade ago (2011), having implications for accounting researchers, reviewers, editorial boards, and those involved in research training.